Dickkopf-3 Causes Neuroprotection by Inducing Vascular Endothelial Growth Factor - Busceti, Carla Letizia; Di Menna, Luisa; Bianchi, Franca; Mastroiacovo, Federica; Di Pietro, Paola; Traficante, Anna; Bozza, Giovanna; Niehrs, Christof; Battaglia, Giuseppe; Bruno, Valeria; Fornai, Francesco; Volpe, Massimo; et al. (Frontiers in Cellular Neuroscience, 2018)
Dickkopf3 (Dkk3) is an atypical member of the Dkk family of Wnt inhibitors, which has been implicated in the pathophysiology of neurodegenerative disorders. However, the role of Dkk3 in mechanisms of cell degeneration and protection is unknown. We used Dkk3 knockout mice to examine how endogenous Dkk3 influences ischemic brain damage. In addition, we used primary cultures of astrocytes or mixed cultures of astrocytes and neurons to investigate the action of Dkk3 on cell damage and dissect the underlying molecular mechanisms. In a model of focal brain ischemia induced by permanent middle cerebral artery occlusion (MCAO) Dkk3-/- mice showed a significantly greater infarct size with respect to their wild-type counterparts at all time points investigated (1, 3 and 7 days after MCAO). Immunohistochemical analysis showed that Dkk3 expression was enhanced at the borders of the ischemic focus, and was predominantly detected in astrocytes. This raised the possibility that Dkk3 produced by astrocytes acted as a protective molecule. We tested this hypothesis using either primary cultures of cortical astrocytes or mixed cortical cultures containing both neurons and astrocytes. Genetic deletion of Dkk3 was permissive to astrocyte damage induced by either oxidative stress or glucose deprivation. In addition, application of human recombinant Dkk3 (hrDkk3) was highly protective against oxidative stress in cultured astrocytes. We tested the hypothesis that the protective activity of Dkk3 was mediated by VEGF. Interestingly, glucose deprivation up-regulated both Dkk3 and vascular endothelial growth factor (VEGF) in cultured astrocytes prepared from wild-type mice. VEGF induction was not observed in astrocytes lacking Dkk3 (i.e., in cultures prepared from Dkk3-/- mice). In mixed cultures of cortical cells, excitotoxic neuronal death induced by a brief pulse with N-methyl-D-aspartate (NMDA) was significantly enhanced when Dkk3 was lacking in astrocytes, whereas post-NMDA addition of hrDkk3 was neuroprotective. Neuroprotection by hrDkk3 was significantly reduced by pharmacological blockade of type-2 VEGF receptors and was mimicked by hrVEGF. These data offer the first evidence that Dkk3 protects both neurons and astrocytes against a variety of toxic insults, and, at least in culture, protection involves VEGF induction.